A New Objective Function for Obstacle Avoidance by Redundant Service Robot Arms. (8th March 2016) - Dede, Mehmet Ismet Can; Maaroof, Omar W.; Tatlicioglu, Enver
The performance of task-space tracking control of kinematically redundant robots regulating self-motion to ensure obstacle avoidance is studied and discussed. As the sub-task objective, the links of the kinematically redundant assistive robot should avoid any collisions with the patient that is being assisted. The shortcomings of the obstacle avoidance algorithms are discussed and a new obstacle avoidance algorithm is proposed. The performance of the proposed algorithm is validated with tests that were carried out using the virtual model of a seven degrees-of-freedom robot arm. The test results indicate that the developed controller for the robot manipulator is successful in both accomplishing the main-task and the sub-task objectives.